Cancer : the emperor of all maladies - Goodman, Barak; Burns, Ken 1953-
Presents a history of cancer, from ancient times to the present day. Includes stories of contemporary patients and examines the latest scientific research which might indicate that we are on the brink of a lasting cure.
episode 1. Magic bullets / directed by Jack Youngelson and Barak Goodman -- episode 2. The blind men and the elephant / directed by Deborah Dickson and Barak Goodman -- episode 3. Finding an Achilles heel / directed by Chris Durrance and Barak Goodman
Keywords: Mukherjee, Siddhartha -- Television adaptations; Cancer -- History; Leukemia -- History